Komunikasi dalam Difusi Inovasi Kerajinan Enceng Gondok di Desa Tuntang, Kabupaten Semarang - Febriana, Kharisma Ayu; Setiawan, Yuliyanto Budi (Universitas Semarang, 2016)
Water hyacinth plants for most residents in the village Tuntang considered a weed in large amounts. Water hyacinth lead to silting in waters such as lakes and ponds, but the diffusion of innovation, a lot of business opportunities that can be produced from water hyacinth handicraft businesses. Villagers Tuntang made of water hyacinth as a craft material that has a high value ekomoni. The method used is qualitative descriptive with case study strategy in the village Tuntang. The result through interpersonal communication to make success in the diffusion process of water hyacinth handicraft innovation for residents in the village Tuntang, Semarang regency.